Multiaspect Soft Sets - Nor Hashimah Sulaiman; Daud Mohamad (Advances in Fuzzy Systems)
We introduce a novel concept of multiaspect soft set which is an extension of the ordinary soft set by Molodtsov. Some basic concepts, operations, and properties of the multiaspect soft sets are studied. We also define a mapping on multiaspect soft classes and investigate several properties related to the images and preimages of multiaspect soft sets.